Ecosystem services, threats, and management practices of wetlands in Morang District of Nepal - Pokharel, Gobinda Prasad; Thakuri, Sudeep (Our Nature, 2024)
Wetlands are gaining much attention recently as they are threatened by multiple stressors; however, detailed ecological and socio-economic studies on these wetlands are limited. In this study, we present an inventory and assess ecosystem services, and conservation status of the wetlands of Morang district in Eastern Nepal. We used the remote sensing data - Google Earth Imagery and official topographic maps – for preparation of inventory and conducted a rapid field survey using a questionnaire, Key Informant Interviews (KIIs) and Focus Group Discussions (FGDs). Provisional and cultural services were analyzed based on field observations and the questionnaire survey. Twenty-four wetlands of 29.4 ha area, ranging from 0.017 to 7.5 ha were recorded. The Sunbarsi wetland is located in the lowest (87 m) and the Chuli Pokhari in the highest (677 m) elevation. Rajarani wetland of Letang (7.5 ha) is the largest wetland in the district. Ten wetlands have high religious value. Wetlands in Morang district are also productive ecosystems providing different types of ecosystem services. They contribute in local economy providing job and business opportunities to locals. Bhulkey wetland of Pathari-1 provides drinking water to 1,938 families. Further, these wetlands are used for irrigation. The wetlands are also providing services to livestock farming, fishing, boating, commercial activities (hotels and shops), and tourism. Cultural, recreational and ecotourism activities in the wetlands are generating revenue locally.